Copper, chromium and zinc content in human semen and its possible effect on sperm quality of fertile and infertile men in the city of Caracas, Venezuela - Foglietta, Luz Marina; Muñoz, Marma Gladys; Alvarado, José (Ciencia)
Copper, chromium and zinc concentrations were determined by atomic absorption spectrometry in semen samples. The concentration of these metals was determined in 43 infertile men and 27 fertile men. Semen quality was evaluated based on the norms established by the World Health Organization. Statistical analysis of the seminal parameters showed significant differences among fertile and infertile men regarding sperm concentration, progressive linear motility and normal morphology. Heavy metal concentrations showed no significant correlation when comparing the results obtained for semen from fertile and infertile men. Overall, the comparison between semen quality and heavy metal concentration showed no correlation; the copper, chromium and zinc concentrations found in the semen samples do not seem to affect sperm quality. This is the first report in Venezuela about the semen concentration of heavy metals.